2022
DOI: 10.1017/s0007485322000323
|View full text |Cite
|
Sign up to set email alerts
|

Sterility ofCydia pomonellaby X ray irradiation as an alternative to gamma radiation for the sterile insect technique

Abstract: The codling moth Cydia pomonella is a major pest of global significance impacting pome fruits and walnuts. It threatens the apple industry in the Loess Plateau and Bohai Bay in China. Sterile insect technique (SIT) could overcome the limitations set by environmentally compatible area-wide integrated pest management (AW-IPM) approaches such as mating disruption and attract-kill that are difficult to suppress in a high-density pest population, as well as the development of insecticide resistance. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
(61 reference statements)
0
17
0
Order By: Relevance
“…This resulted in the moths receiving a dosage of 366 Gy of irradiation, as our previous investigation demonstrated that the application of 366 Gy of X-ray irradiation effectively induced complete sterility in male codling moths. 6,16 2.3 Flight ability 2.3.1 Flight performance of both genders of coding moth at different ages To determine the flight performance of male and female moth at different ages, we used the FXMD-24-USB insect flight information system (Henan Hebi Jiaduoke Industry and Trade Co., Ltd, Hebi, Henan, China). We kept the daily-emerging adult females and males separately in rearing boxes and fed them cotton balls in 10% honey water every day.…”
Section: Irradiationmentioning
confidence: 99%
See 4 more Smart Citations
“…This resulted in the moths receiving a dosage of 366 Gy of irradiation, as our previous investigation demonstrated that the application of 366 Gy of X-ray irradiation effectively induced complete sterility in male codling moths. 6,16 2.3 Flight ability 2.3.1 Flight performance of both genders of coding moth at different ages To determine the flight performance of male and female moth at different ages, we used the FXMD-24-USB insect flight information system (Henan Hebi Jiaduoke Industry and Trade Co., Ltd, Hebi, Henan, China). We kept the daily-emerging adult females and males separately in rearing boxes and fed them cotton balls in 10% honey water every day.…”
Section: Irradiationmentioning
confidence: 99%
“…4 As one of the best-known representatives of tortricids that threaten the apple industry in the Loess Plateau and Bohai Bay, 5 this pest has been identified as an invasive alien species, and has been included in the key management list of invasive alien species issued by six departments including the Ministry of Agriculture and Rural Affairs of China. 6 Currently, various methods have been used to control C. pomonella, including agricultural, mechanical, chemical, and biological measures. 7 However, environmentally-friendly methods such as agricultural practices, pheromone-mediated mating disruption, and attract-kill have their limitations when dealing with highdensity of pest population.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations